How Does Impostor Phenomenon Relate to Job Performance? - Wina Salsabila; Rostiana Rostiana (Tazkiya Journal of Psychology, 2025)
Impostor phenomenon is a psychological condition experienced by individuals who are competent in their field but feels insecure about their abilities. Individuals with impostor phenomenon have low career struggles, making it difficult to get into leadership positions. Research related to the performance of individuals with impostor phenomenon is limited. Therefore, the objective of this study was to conduct further research regarding the performance of professional workers with impostor phenomenon on three performance variables, namely task performance, contextual performance, and counterproductive work behavior. A total of 146 valid responses were obtained through four self-report instruments, the Individual Work Performance Questionnaire, the Perfectionism Cognitions Inventory, the Perceived Supervisory Support Scale, and the Clance Impostor Phenomenon Scale. The respondents included 71 participants with high impostor phenomenon and 75 with low impostor phenomenon. After conducting correlation analysis, this study shows that there are differences in performance between the high and low impostor phenomenon groups. The high impostor phenomenon group tends to have higher job performance score, but with higher counterproductive work behavior. Meanwhile, the low impostor phenomenon group has higher task performance with better quality results. We also found that perfectionism and perceived supervisor support have a significant correlation with the performance of the high impostor phenomenon group. In order to provide more comprehensive understanding, this study also includes discussions and suggestions regarding research variables.